Poly(lactic acid)/ poly(ε-caprolactone) blends: the effect of nanocalcium carbonate and glycidyl methacrylate on interfacial characteristics - Negaresh, Mohammadmahdi; Javadi, Azizeh; Garmabi, Hamid (Frontiers in Materials, 2024)
To expand the potential applications of polylactic acid (PLA), it is essential to incorporate a highly flexible polymer into the blend. Polycaprolactone (PCL) is an ideal choice due to its ductility and biodegradability. However, blending PLA with PCL resulted in weak mechanical properties. To address this issue, glycidyl methacrylate (GMA) and nano calcium carbonate (NCC) were introduced to enhance the adhesion at the interface between PLA and PCL. SEM images provided clear visual evidence of the impact of GMA and NCC on the morphology of the blend. Both components were effective in reducing the size of the dispersed PCL phase, shrinking it to approximately half the size of the original blend. Spectroscopic analysis revealed that GMA caused a reaction between its epoxy group and the hydroxyl and carboxyl groups of PLA and PCL. This reaction led to the formation of strong peaks in the 6.5 to 7.5 range in 1 H NMR, as well as peaks at 76 and 139 ppm in 13 C NMR. These findings were further corroborated by FT-IR, which demonstrated that NCC, despite its surface coating, did not create any new bonds. Rheological studies further demonstrated the positive effects of GMA and NCC. Both the storage modulus (G') and complex viscosity (η*) of the blends increased, showing improved post-processing performance. Investigation into the shear-thinning behavior of the uncompatibilized blends revealed that NCC caused a significant decrease in complex viscosity at higher frequencies, indicating the disruption of the nanoparticle network. The power-law slope was measured to be 0.62. In contrast, the blend containing the compatibilizer demonstrated a moderate decrease in viscosity, with a power-law slope of 0.36. To analyze the behavior of the PLA/PCL blends in the presence of compatibilizers and nanoparticles at intermediate frequencies, the Palirene model was utilized. The superior integrity of the compatibilized blend was effectively demonstrated by the model, which showed enhanced stress transfer and phase relaxation.